Análise dos fatores influentes nos riscos de descontinuidade na cadeia de peças de reposição automotivas - Silva, Antonio Lopes Nogueira da [UNESP] (2015)
The Brazilian market for light vehicles has a fleet where 43% of vehicles have up to five years of manufacture, causing the spare sectors of automotive parts move billions a year. Still, it is common to lack of spare parts, which requires management of the supply chain to mitigate the discontinuity risks. This paper analyzes the risks of supply in the chain of spare parts for light vehicle dealerships networks by prioritizing the variables that influence the supply disruption in this chain. The applied method presents a qualitative and quantitative approach with the concessionaires of the South Fluminense region. These dealerships represent fourteen major brands operating in Brazil with a sales volume of around 93% in 2015. The most important variables are staff training, communication and lead time. The survey also shows that organizational factors are relevant to the spare parts supply which is not mentioned in the literature, together with the factors related to the supply chain.